CO2-Catalysed conversion of carbohydrates to 5-hydroxymethyl furfural. Issue 23 (16th September 2016) - Lee, Roland; Harris, Jesse; Champagne, Pascale; Jessop, Philip G.
Abstract : CO2 in water catalyzes the conversion of cellulose, starch, xylan, or glucose to HMF. Abstract : The conversion of sugars to furans has been gaining attention in recent years as a potential source of renewable chemical building blocks. This work considers the viability of CO2 as an acid catalyst for the conversion of carbohydrates to 5-hydroxymethyl furfural (5-HMF). In addition, the effects of secondary solvents for the separation of the produced 5-HMF from the aqueous reaction mixtures are explored. The addition of salts as a means of phase separation to improve the 5-HMF yield was also investigated. The yield of 5-HMF for CO2 -catalyzed glucose conversions was increased from 18% to 64% by varying the concentrations of sugar, salt and choice of secondary solvent. This method was also applied to starch, xylan, and cellulose, and was able to achieve 55%, 51% and 22% respectively. This work shows that high yields of 5-HMF could be achieved through the use of CO2 -catalyzed carbohydrate conversions.